*Ubuntu* ethics and moral problems in traditional bone-healing - Cornelius Ewuoso; Ademola Kazeem Fayemi; Kiarash Aramesh (Journal of Global Health Reports)
Traditional bone-healing (TBH) remains a widespread practice for various orthopaedics anomalies in many African countries. Despite the patronage frequency of TBH by patients with orthopaedic crises, the ethical issues involved in TBH are yet to gain scholarly attention. In this article, the moral issues in TBH are exposed with critical inquisition on what an *Ubuntu* ethic would prescribe for addressing some of the moral problems in alternative orthopaedic practices. To the extent that parts of TBH might be a useful first aid practice in lieu of orthodox orthopaedic infrastructure, this article finds as morally questionable, delayed referrals by traditional bone-healers resulting in late diagnosis of osteosarcoma and preventable loss of limbs, and sometimes death. Also identified are the pseudoscientific aspects of TBH and a disregard for conflict of interests in the supernatural-profane bone-healing process. This article appeals to *Ubuntu* relational ethic in prescribing solutions to some moral problems involved in TBH. The article concludes that the value for communal relationship in *Ubuntu* ethic is an attractive framework that can ground orthopaedic care that is respectful of conflicts of interests, and individual’s personhood without an attenuation of the common public orthopaedic health good in Africa and beyond.